Project Management as a B2B Service in the automotive development process - Reiche, Finn; Schmidtner, Markus; Marx, Emanuel; Matzner, Martin; Timinger, Holger (Proceedings of the 17th International Conference on Wirtschaftsinformatik (WI), 2022)
The German automotive industry currently not only faces the effects of COVID-19 on the supply chain but also a disruption by new technologies and new competitors. In order to rise to these challenges, project management must be improved and partners along the supply chain must be integrated more tightly. One part in accomplishing this, is to provide an interorganizational project management service between all involved partners. In order to improve, we first have to understand the current implementation of project management services between the OEM and suppliers and examine what the different actors expect from these services. This working paper addresses this issue by conducting a literature review as well as interviews with project management experts in the automotive industry.<br
Keywords: project management; B2B Services; automotive; digital industrial services